2022
DOI: 10.3390/ijms231911033
|View full text |Cite
|
Sign up to set email alerts
|

The Chromosome Number and rDNA Loci Evolution in Onobrychis (Fabaceae)

Abstract: The evolution of chromosome number and ribosomal DNA (rDNA) loci number and localisation were studied in Onobrychis Mill. Diploid and tetraploid species, as well as two basic chromosome numbers, x = 7 and x = 8, were observed among analysed taxa. The chromosomal distribution of rDNA loci was presented here for the first time using fluorescence in situ hybridisation (FISH) with 5S and 35S rDNA probes. Onobrychis species showed a high polymorphism in the number and localisation of rDNA loci among diploids, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…from France and Turkmenistan, respectively (Abou-El-Enain, 2002), as well as O. subacaulis Boiss. from Poland (Yucel et al, 2022). In addition, it has been suggested that the basic chromosome count x = 8 is associated with the annual Onobrychis species while x = 7 is more frequent in perennial species (Abou-El-Enain, 2002;Díaz-Lifante et al, 1992;Gömürgen, 1996).…”
Section: Nomentioning
confidence: 99%
See 2 more Smart Citations
“…from France and Turkmenistan, respectively (Abou-El-Enain, 2002), as well as O. subacaulis Boiss. from Poland (Yucel et al, 2022). In addition, it has been suggested that the basic chromosome count x = 8 is associated with the annual Onobrychis species while x = 7 is more frequent in perennial species (Abou-El-Enain, 2002;Díaz-Lifante et al, 1992;Gömürgen, 1996).…”
Section: Nomentioning
confidence: 99%
“…from France and Turkmenistan, respectively (Abou‐El‐Enain, 2002), as well as O. subacaulis Boiss. from Poland (Yucel et al., 2022).…”
Section: Origin Distribution and Cytologymentioning
confidence: 99%
See 1 more Smart Citation
“…In these regions, Onobrychis species are cultivated to produce protein-rich animal food. Also, these species have a crucial infuence on the environment of soil by developing its nutritive value (Talebi et al, 2020;Hadadi et al, 2022;Yucel et al, 2022). Sainfoin has the potential to enhance the diversity and sustainability of agroecosystems by providing multiple revenue streams, numerous ecosystem services, and the flexibility to adapt management strategies to climate change (Craine et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In the final publication of this Special Issue, Yucel et al [ 36 ] show the comparative analyses of some aspects of karyotype organisation in the two subgenera of Onobrychis (sainfoins). This legume genus contains numerous species, some of them economically valuable as forage or even crops, whose phylogenetic relations are complex and not fully resolved.…”
mentioning
confidence: 99%